2007
DOI: 10.1111/j.1528-1167.2007.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Attitudes and Practice toward Epilepsy among Adults in BaVi, Vietnam: First Report from the Population‐Based EPIBAVI Study

Abstract: Summary:Purpose: We conducted a survey to assess knowledge, attitudes, and practice toward epilepsy in a populationbased study in a rural district of Vietnam.Methods: We utilized an established knowledge-attitudespractice questionnaire. This was applied by trained surveyors in face-to-face interviews of 2005 randomly selected adult residents (19-71 years of age) of the BaVi district, 60 km west of Hanoi.Results: Of the respondents, 67.0% had heard about epilepsy, 52.1% had known someone with seizures, and 49.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
0
19
1
1
Order By: Relevance
“…Since persons with more negative attitudes toward epilepsy (as a type of insanity) and possible life success of a child with epilepsy held significantly more negative views toward a child with epilepsy, while experiential factors (knowing a person with epilepsy, witnessing an event) did not reach a statistical significance, this outcome could be a consequence of common or similar origin of all three views. The USA studies revealed an improvement from 24% (1949) to 6% (1979) [10], Czech from 29% (1981) to 13% (1987) [22], German from 31% (1967) to 15% (1995) [39], Hungarian from 19% (1994) to 16.5% (2000) [23], while opposite trends were reported in Italy from 11% (1983) to 34% (1985) [39] and in Vietnam from 18.7% in 2003 [31] to 36.3% in 2005 [33].…”
Section: The Population's Attitude Toward Epilepsy and Persons With Econtrasting
confidence: 55%
See 2 more Smart Citations
“…Since persons with more negative attitudes toward epilepsy (as a type of insanity) and possible life success of a child with epilepsy held significantly more negative views toward a child with epilepsy, while experiential factors (knowing a person with epilepsy, witnessing an event) did not reach a statistical significance, this outcome could be a consequence of common or similar origin of all three views. The USA studies revealed an improvement from 24% (1949) to 6% (1979) [10], Czech from 29% (1981) to 13% (1987) [22], German from 31% (1967) to 15% (1995) [39], Hungarian from 19% (1994) to 16.5% (2000) [23], while opposite trends were reported in Italy from 11% (1983) to 34% (1985) [39] and in Vietnam from 18.7% in 2003 [31] to 36.3% in 2005 [33].…”
Section: The Population's Attitude Toward Epilepsy and Persons With Econtrasting
confidence: 55%
“…Fear of seizures was favored by those 36-45 years old and injuries and rejection by others by those 26-35 years of age. Young participants (26)(27)(28)(29)(30)(31)(32)(33)(34)(35) selected limited activities least frequently, and those 36-45 years old most frequently. Those with primary school level of education favored seizures, those with secondary school level injuries and those with a university degree the fear of seizures.…”
Section: Population's Understanding Of Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier quantitative studies conducted in Vietnam indicate low levels of understanding about causes and treatment of epilepsy, and prevailing negative attitudes [24,25]. To appreciate more fully the contextually driven meaning of such responses, the present investigation employs an ethnographic approach to facilitate the exploration of local ontologies of epilepsy, lay beliefs and experiences of people with epilepsy and their family members in treatment of epilepsy, impact of epilepsy, attitudes toward epilepsy and attitudes toward disclosure of epilepsy.…”
Section: Study Context Methods and Samplementioning
confidence: 99%
“…In addition, a study on opinions of people towards epilepsy found that and 10% of respondents thought that epilepsy was a form of insanity, 36.3% of respondents would object to their children playing with someone with seizures and 82.0% would object to their children marrying someone with epilepsy (Tuan, Cuong et al 2007). The lack of awareness and stigma towards mental health also affects health seeking behaviour of people with mental health problems.…”
Section: Mental Healthmentioning
confidence: 99%